PERLINDUNGAN HUKUM TERHADAP PERANAN MASYARAKAT SEBAGAI PARA PEMEGANG SAHAM DALAM KEGIATAN USAHA SUATU PERUSAHAAN GUNA MENCAPAI KESEJAHTERAAN - Aliandu, Fx. Denny Satria (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
Indonesia is a country that has a good capacity for various fields, which include political, economic, social, cultural, defense and security, can giving a function to processing Indonesian growth and progress of a country reviewing of the economic development of the country. The role of the company in the process of economic development of the people of Indonesian can be do by involving to participate in the activities of the company, and the entry in the companys organizational structure or by investing in a company. People who participate in the activities of investment companies known as shareholders or investors. The shareholder is helpful all the aspect of company activities, such as helping in the company progressing and welfarestate. In the practice of this company will be explored more specifically, where the attentionÂ of company performance that involve the society to be active in the practice of the company activities and make a welfaresatete. But the problem is dynamic processing of the companys performance, because the companys performance is not always will be remaining static.